ChemInform Abstract: Direct and Indirect Single Electron Transfer (SET)‐Photochemical Approaches for the Preparation of Novel Phthalimide and Naphthalimide‐Based Lariat‐Type Crown Ethers. Issue 40 (30th September 2014) - Cho, Dae Won; Mariano, Patrick S.; Yoon, Ung Chan
Abstract Review: 87 refs.